2015
DOI: 10.1371/journal.pone.0127045
|View full text |Cite|
|
Sign up to set email alerts
|

Alternating Hemiplegia of Childhood: Retrospective Genetic Study and Genotype-Phenotype Correlations in 187 Subjects from the US AHCF Registry

Abstract: Mutations in ATP1A3 cause Alternating Hemiplegia of Childhood (AHC) by disrupting function of the neuronal Na+/K+ ATPase. Published studies to date indicate 2 recurrent mutations, D801N and E815K, and a more severe phenotype in the E815K cohort. We performed mutation analysis and retrospective genotype-phenotype correlations in all eligible patients with AHC enrolled in the US AHC Foundation registry from 1997-2012. Clinical data were abstracted from standardized caregivers’ questionnaires and medical records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
5
51
0
Order By: Relevance
“…The precise cause of these clinical variabilities in AHC is not yet known except for partial correlations between the genotype and phenotype as reported by several groups. [14][15][16][17] We found progressive localized brain atrophy in some patients, particularly where severe deterioration was evident. 18,19 We investigated Japanese patients with AHC to assess if they had structural brain abnormalities and to determine the critical brain structural differences between a group with irreversible severe deterioration and one without severe deterioration.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The precise cause of these clinical variabilities in AHC is not yet known except for partial correlations between the genotype and phenotype as reported by several groups. [14][15][16][17] We found progressive localized brain atrophy in some patients, particularly where severe deterioration was evident. 18,19 We investigated Japanese patients with AHC to assess if they had structural brain abnormalities and to determine the critical brain structural differences between a group with irreversible severe deterioration and one without severe deterioration.…”
Section: Introductionmentioning
confidence: 69%
“…However, the relationship between the clinical course and changes in brain MRI findings has not yet been established in patients with AHC. The precise cause of these clinical variabilities in AHC is not yet known except for partial correlations between the genotype and phenotype as reported by several groups …”
Section: Introductionmentioning
confidence: 99%
“…While these syndromes share symptomatic profiles including triggered episodes, a strong genotype-to-phenotype correlation exists within this spectrum. In fact, 60% of patients worldwide diagnosed clinically as AHC have one of three unique ATP1A3 missense mutations, leading to amino acid changes D801N, E815K, or G947R (Heinzen et al, 2012;Viollet et al, 2015). Only symptomatic treatment options exist for patients diagnosed with AHC, including benzodiazepines and other antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a series of publications have suggested that ATP1A3 mutations are associated with a wide clinical spectrum, and that they are one of the “commoner rare diseases” . A diagnosis of ATP1A3 ‐related disease has specific management implications, including avoidance of triggers and pharmacological prophylaxis of attacks .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Subsequently, a series of publications have suggested that ATP1A3 mutations are associated with a wide clinical spectrum, and that they are one of the "commoner rare diseases". [4][5][6] A diagnosis of ATP1A3-related disease has specific management implications, including avoidance of triggers and pharmacological prophylaxis of attacks. 7 Routine blood tests and brain MRI are typically normal; hence, recognition of the disorder on clinical grounds is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%